Interregional comparative analysis of farmers’ perceptions and expectations of climate change - Acibuca, Veysi; Kaya, Aybüke; Kaya, Tuğçe (Italian Journal of Agronomy, 2022)
This study looked into the relationship and effects of agricultural activities in different regions of Turkey on climate change. This study aims to determine farmer awareness of climate change and its effects, as well as farmer adaptation capabilities in different regions of Turkey against climate change, and to develop extension and policy tools based on the findings. Data were collected through face-to-face surveys with farmers in the provinces where the research was conducted. In this context, a proportional sampling survey of 418 farmers was conducted. The collected information was subjected to factor analysis and the independent t-test. According to the findings, farmers associate climate change with precipitation, and the effect of precipitation and the risks it poses in increasing or decreasing crop yields are of particular concern. Farmers in the Southeastern Anatolia Region are more concerned about heat and drought than farmers in the Mediterranean Region. Furthermore, producers believe that human-caused factors and economic development have a greater impact on climate change than agricultural activities. Farmers in research areas are concerned that climate change will increase migration from rural areas and the decline of forests and animal species. As a result, raising individual awareness and utilising new technology in rural areas is critical. Farmers’ awareness of new and environmentally friendly agricultural techniques must be raised to increase their use. Highlights - Farmers associate climate change with drought. - According to the farmers, the leading factors causing climate change are human-induced factors that disrupt the ecological balance. - The most important concern regarding the effects of climate change is that production costs will increase. - Farmers are reluctant to implement adaptation or mitigation methods that can be developed against climate change.